Compression zone formation in plasma streams generated by MPC device operating with gases of different mass - Marchenko, A.K.; Ladygina, M.S.; Garkusha, I.E.; Petrov, Yu.V.; Solyakov, D.G.; Cherednichenko, T.N.; Makhlaj, V.A.; Chebotarev, V.V.; Staltsov, V.V.; Yelisyeyev, D.V.; Krauz, V.I. (Вопросы атомной науки и техники, 2014)
This paper presents analysis of compression zone formation in plasma streams generated by compact magnetoplasma compressor operating with argon and helium. The main aim for this investigation is characterization of plasma in compression zone in dependence on initial concentration of working gas. The initial concentration was changed by variation of residual gas pressure in vacuum chamber. The mass flow rate was kept constant. It was possible due to 10 times difference between He and Ar masses. Thus, decrease of residual pressure from 10 Torr for helium till 1 Torr for argon allows keep the mass flow rate in spite the initial density value decreases in 10 times. The temporal and spatial distributions of plasma density were measured in plasma stream and in the compression region in both cases. It was shown with spectroscopy that plasma density in compression region increased up to 3.5 times with decreasing initial concentration in 10 times. The obtained result is in agreement with analytical estimation that follows from the Bernoulli equation. Plasma dynamics in compression region is also discussed. Статья посвящена анализу формирования зоны компрессии в плазменных потоках, генерируемых компактным магнитоплазменным компрессором МПК, используя в качестве рабочего газа аргон и гелий. Основной целью данной работы являлся анализ параметров плазмы в зоне компрессии и их зависимость от начальной концентрации рабочего газа. Начальная концентрация изменялась путем выбора величины давления остаточного газа в вакуумной камере. Массовый расход газа остался постоянным, благодаря 10-кратной разнице масс аргона и гелия. Таким образом, уменьшение остаточного давления с 10 Торр для гелия до 1 Торр для аргона позволяет сберечь массовый расход при уменьшении начальной концентрации в 10 раз. Временные и пространственные распределения электронной плотности плазмы в области компрессии были измерены для двух случаев. Спектроскопические измерения показали, что плотность плазмы в области сжатия увеличилась в 3,5 раза при уменьшении начальной концентрации рабочего газа в 10 раз, что согласуется с аналитическими оценками из уравнения Бернулли. Также представлены исследования динамика плазмы в зоне компрессии. Стаття присвячена аналізу формування компресійної зони в плазмових потоках, що генеруються компактним магнітоплазмовим компресором МПК, використовуючи в якості робочого газу аргон та гелій. Основною метою роботи є аналіз параметрів плазми в зоні компресії та їх залежність від початкової концентрації робочого газу. Початкова концентрація змінювалася за допомогою зміни тиску залишкового газу у вакуумній камері. Масовий розхід газу залишався постійним, завдяки 10-разовій різниці між масами аргону та гелію. Таким чином, зменшення залишкового тиску з 10 Торр для гелію до 1 Торр для аргону дозволяє зберегти масовий розхід в той час як значення початкової концентрації зменшується в 10 разів. Часові та просторові розподіли електронної густини плазми вимірювались в зоні компресії для обох випадків. Часові та просторові розподіли густини плазми були виміряні в плазмовому потоці та зоні компресії обох випадках. Спектроскопічні вимірювання показали, що електронна густина плазми в зоні компресії збільшується в 3,5 рази при зниженні початкової концентрації в 10 разів, що узгоджується з аналітичними оцінками з рівняння Бернуллі. Також досліджувалася динаміка плазми в зоні компресії.